2019
DOI: 10.1080/14686996.2019.1625722
|View full text |Cite
|
Sign up to set email alerts
|

Cryogenic study of the magnetic and thermal stability of retained austenite in nanostructured bainite

Abstract: First magnetic characterization of a recently developed generation of carbide free bainitic steels, known as Nanobain, has been performed. Stability of its retained austenite at cryogenic temperatures has been studied by means of X-ray diffraction, microscopy, dilatometry and magnetic measurements. Two morphologies for this phase (blocky-type and film-type) appear in a different proportion depending on the chemical composition and the applied thermal treatment. Inhibition of the martensitic transformation, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…The other is blocky martensite/austenite (M/A) constituents, which have poor stability and are easily transformed into untempered brittle martensite under stress, leading to volume expansion and crack initiation, thereby weakening the toughness and wear resistance. [13][14][15][16][17][18][19] However, Efremenko et al believed that the existence of a large amount of unstable RA was beneficial to the wear resistance of steel. [20] The results showed that the steel containing %60 vol% unstable blocky RA was 1.5 times more wear resistant than the steel containing 10-39 vol% NB and 49-55 vol% stable RA.…”
Section: Introductionmentioning
confidence: 99%
“…The other is blocky martensite/austenite (M/A) constituents, which have poor stability and are easily transformed into untempered brittle martensite under stress, leading to volume expansion and crack initiation, thereby weakening the toughness and wear resistance. [13][14][15][16][17][18][19] However, Efremenko et al believed that the existence of a large amount of unstable RA was beneficial to the wear resistance of steel. [20] The results showed that the steel containing %60 vol% unstable blocky RA was 1.5 times more wear resistant than the steel containing 10-39 vol% NB and 49-55 vol% stable RA.…”
Section: Introductionmentioning
confidence: 99%